Portret i marzenie - Panek, Sylwia (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
In this article, the author discusses and reviews Andrzej Lam’s book Portrety i spotkania (Pułtusk–Warszawa 2014) which is a collection of studies of German poets from the Middle Ages until the mid-20th century. The author highlights the coherence of the publication consisting of texts written in the past 30 years. Originally, they were allocated different functions, but in Lam’s book they seem homogenous and mutually complementary. Lam’s homogenous position results from the writer’s attitude: very skilfully, he makes use of structuring tools, heading towards a hermeneutic desire to provide an outline of the writers emerging from the texts and connected with them. The author also presents the literary criticism aspect of the book: in the second part, Lam is predominantly a historian of literary criticism and its active participant.